Synthesis, characterization, and molecular modeling of novel 1,3,4-oxadiazole derivatives of mefenamic acid - Bhat Mashooq A.; Naglah Ahmed M.; Bakheit Ahmed Hassan; Al-Omar Mohamad A. (Polish Journal of Chemical Technology, 2024)
A novel series of 1,3,4-oxadiazole derivatives of mefenamic acid was obtained by reacting hydrazones of mefenamic acid with anhydrous acetic anhydride. The mefenamic hydrazones were obtained by reacting different substituted aldehydes with mefenamic acid hydrazide. All the compounds were characterized by spectral data and elemental analysis. Molecular docking studies of all the compounds were performed against COX-1/COX-2 enzymes. Compound 4 and compound 10 were found to have the highest potential to bind with COX-1 while compound 3, compound 6, and compound 10 were found to have the highest potential to bind with COX-2 enzyme.